URGENSI KURIKULUM PENDIDIKAN BERBASIS INKLUSIF PADA PROSES PEMBELAJARAN DI SEKOLAH DASAR NEGERI - Miftah Sabillah; Nabilla Al Zahira Najibullah; Sapto Cahyono; Auliya Nabaul Insani; Dede Indra Setiabudi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
In the current era of development and progress of education, challenges andopportunities will continue to exist. And one of them is inclusive education. Thisstudy aims to dig deeper into the concept of inclusive education. Because inclusiveeducation emphasizes the importance of builing learning that supports equality forall students and the application of cultural values that applay in the area. Thisresearch method uses a qualitative descriptive method with literature studies ininclusive learning, equality and culture values will involve various elements andstrategies. Including the use of curriculum learning methods participation fromparents, third parties, and diverse assessments. By uniting all related element sothat teachers can create a learning atmosphere that supports equality for allstudents. And allows to bring out their potential.